2011
DOI: 10.1007/s10646-011-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of mercury in macroinvertebrates and fishes from streams of two contrasting forested landscapes in the eastern United States

Abstract: Controls on mercury bioaccumulation in lotic ecosystems are not well understood. During 2007–2009, we studied mercury and stable isotope spatial patterns of macroinvertebrates and fishes from two medium-sized (<80 km2) forested basins in contrasting settings. Samples were collected seasonally from multiple sites across the Fishing Brook basin (FBNY), in New York’s Adirondack Mountains, and the McTier Creek basin (MCSC), in South Carolina’s Coastal Plain. Mean methylmercury (MeHg) concentrations within macroinv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 58 publications
7
36
0
Order By: Relevance
“…In general, MeHg in these invertebrates tended to be highest in low pH and high DOC systems, as has been observed in other studies (Rennie et al, 2005;Chételat et al, 2011;Riva-Murray et al, 2011;Tsui and Finlay, 2011;Clayden et al, 2014) likely reflecting the role of these variables in promoting Hg methylation and/or bioavailability to the base of food webs. Aqueous TOC for the New Brunswick lakes were all below a DOC threshold of 8.5 mg/L observed by French et al (2014) above which there appears to be reduced bioavailability of Hg to amphipods from Arctic lakes.…”
Section: Mercury Concentrations In Invertebratessupporting
confidence: 82%
“…In general, MeHg in these invertebrates tended to be highest in low pH and high DOC systems, as has been observed in other studies (Rennie et al, 2005;Chételat et al, 2011;Riva-Murray et al, 2011;Tsui and Finlay, 2011;Clayden et al, 2014) likely reflecting the role of these variables in promoting Hg methylation and/or bioavailability to the base of food webs. Aqueous TOC for the New Brunswick lakes were all below a DOC threshold of 8.5 mg/L observed by French et al (2014) above which there appears to be reduced bioavailability of Hg to amphipods from Arctic lakes.…”
Section: Mercury Concentrations In Invertebratessupporting
confidence: 82%
“…Both areas are sensitive to the atmospheric deposition of Hg from distant sources (Driscoll et al 2007; Evers et al 2007; Glover et al 2010; NYDOH 2010; SCDHEC 2010). Previously, Riva-Murray et al (2011) showed increasing biotic MeHg with consumer trophic position in both areas, and a strong positive relation with aqueous (filtered) MeHg (FMeHg) concentration across the topographically-heterogeneous Fishing Brook study area. Here, we (1) compare carbon isotope signatures and MeHg concentrations of sympatric primary consumers having distinct feeding strategies, (2) quantify the contribution of dietary carbon to variation in primary consumer MeHg concentration at the stream reach scale, after accounting for trophic position, (3) describe variation among sites in carbon signatures and MeHg concentrations of secondary consumers, and (4) quantify the contribution of dietary carbon to observed spatial variation in secondary consumer MeHg concentration, after accounting for consumer trophic position and stream water FMeHg.…”
Section: Introductionmentioning
confidence: 89%
“…Both are known to consume the targeted primary consumers and are, themselves, prey of fish collected for this study. Fish were collected from throughout wadable reaches, and along edge habitat of nonwadable reaches, by electrofishing and netting, as described in Riva-Murray et al (2011). Selected minnows (family Cyprinidae) were targeted for regional comparisons because of their similar habitats and feeding strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Aquatic mosses were believed to be a good potential indicator of Hg accumulation because of their relatively high THg concentrations (Fig. 4), their predisposition to cell surface adsorption of inorganic heavy metals such as mercury, [62,144,145] and their proven use as biomonitors of atmospheric deposition of Hg. [144,146,147] Knowing this, we expected to see differences that aligned with our Hg results for brook trout, crayfish, and macroinvertebrates.…”
Section: Mercury As An Indicator Of Changementioning
confidence: 99%